Problems and Solutions in the Process of Learning the English Equivalents of the Parts of Body Movement in Uzbek Language (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The word form, the semantic structure of interlaced words and their use in speech are various in different languages. When verbs representing body movement in Uzbek and English were compared, it was found that both languages had similar and different aspects in the expression of such verbs.